Effects of plant diversity and big-sized trees on ecosystem function in a tropical montane evergreen broad-leaved forest - Li, Shuaifeng; Lang, Xuedong; Huang, Xiaobo; Wang, Yanhong; Tang, Rong; Liu, Wande; Xu, Chonghua; Su, Jianrong (Frontiers in Ecology and Evolution, 2023)
Scale dependencies play a vital role in defining the biodiversity-ecosystem functioning relationship in forest ecosystems, which varies based on the magnitude of multiple plant diversity attributes, soil properties, and aboveground biomass in forest ecosystems. However, the effects of plant diversity and big-sized trees on the relationship between plant diversity and aboveground biomass across different scales remain unclear in forest ecosystems. Based on a 30-ha tropical montane evergreen broad-leaved forest dynamics plot in Yunnan province, China, we comparatively analyzed the importance of scale-dependent effects of multiple plant diversity attributes, soil properties, neighborhood competition intensity and aboveground biomass of big-sized trees, as well as stand structural complexity on aboveground biomass of all woody individuals. The aim is therefore to identify the main predictors for sustaining aboveground biomass of all woody individuals, considering multiple biotic and abiotic factors jointly, as well as underlying mechanisms. Our results suggest that indicators such as species richness and phylogenetic diversity did not strongly contribute to aboveground biomass of all woody individuals with increasing spatial scales, while aboveground biomass of big-sized trees exhibited the greatest contribution to aboveground biomass of all woody individuals. Stand structural complexity, characterized by variances in woody plant diameter at breast height, also contributed more to aboveground biomass of all woody individuals indirectly via neighborhood competition intensity and aboveground biomass of big-sized trees. Contributions of functional dispersion and community-weighted mean of leaf phosphorus concentration to aboveground biomass of all woody individuals became stronger with increasing spatial scales. Neighborhood competition intensity exhibited a negative linear relationship with aboveground biomass of all woody individuals at the smallest scale, but it affected positively aboveground biomass of all woody individuals across spatial scales, likely due to indirect effects via aboveground biomass of big-sized trees.Results suggest that big-sized trees will likely become more important in biodiversity maintenance and ecosystem function management as deforestation and forest degradation.